Nanobodies As Tools to Understand, Diagnose, and Treat African Trypanosomiasis - Stijlemans, Benoit; De Baetselier, Patrick; Caljon, Guy; Van Den Abbeele, Jan; Van Ginderachter, Jo A.; Magez, Stefan (Frontiers in Immunology, 2017)
African trypanosomes are strictly extracellular protozoan parasites that cause diseases in humans and livestock and significantly affect the economic development of sub-Saharan Africa. Due to an elaborate and efficient (vector)-parasite-host interplay, required to complete their life cycle/transmission, trypanosomes have evolved efficient immune escape mechanisms that manipulate the entire host immune response. So far, not a single field applicable vaccine exists, and chemotherapy is the only strategy available to treat the disease. Current therapies however exhibit high drug toxicity and an increased drug resistance is being reported. In addition, diagnosis is often hampered due to the inadequacy of current diagnostic procedures. In the context of tackling the shortcomings of current treatment and diagnostic approaches, Nanobodies (Nbs, derived from the heavy chain-only antibodies of camels and llamas) might represent unmet advantages compared to conventional tools. Indeed, the combination of their small size, high stability, high affinity and specificity for their target and tailorability, represents a unique advantage, which is reflected by their broad use in basic and clinical research to date. In this article, we will review and discuss (i) diagnostic and therapeutic applications of Nbs that are being evaluated in the context of African trypanosomiasis (AT), (ii) summarize new strategies that are being developed to optimize their potency for advancing their use and (iii) document on unexpected properties of Nbs, such as inherent trypanolytic activities, that besides opening new therapeutic avenues, might offer new insight in hidden biological activities of conventional antibodies.